Manajemen Pendidikan Karakter Melalui Projek Penguatan Profil Pelajar Pancasila di SMP Negeri 1 Playen Gunungkidul - Suryantari, Dania Suryantari; Supriyoko (Media Manajemen Pendidikan, 2024)
Character education in the independent curriculum is called the Pancasila Student Profile. This form of implementing Pancasila Student Profile character education can be carried out both intra-curricular, extra-curricular and co-curricularly. Co-curricular implementation in the form of project activities is a new thing in the independent curriculum. This study aims to describe the management of character education through the Pancasila Student Profile Strengthening Project. This research is qualitative research conducted at Playen 1 Public Middle School for the 2022/2023 school year. The research data was obtained through observation, interviews, and document study. The research subjects in this study were school principals, teachers, and students. Test the validity of using triangulation techniques. The results of the study show that character education management through the Pancasila Student Profile Strengthening Project at the planning stage starting from the formation of the team; identification of school readiness level; designing dimensions, themes, time allocation; preparation of project modules; and design a reporting strategy. The organizing stage consists of delegating tasks within the team. The implementation phase is by what has been planned according to the activity syntax to reporting in the project report card. At the supervision stage, the principal has carried out his duties but there is no supervision manual yet. The last stage is evaluating the implementation of the Pancasila Student Profile Strengthening Project so that a follow-up plan is obtained for the future.